PENGARUH HARGA, PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PENGGUNA JASA TRANSPORTASI ONLINE GOJEK - Dini Kharismasuni; Edi Wibowo; Setyaningsih Sri Utami (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study was to analyze the significance effect of price, service and promotion on the decisions of users of Gojek online transportation services in Banjarsari District, Surakarta City. This research is a survey of users of Gojek transportation services in Surakarta. The sample is 100 respondents used accidental sampling technique. The data collection technique used questionnaires and literature study. The data analysis technique used multiple linear regression. The results showed that the price has a significant effect on Gojek transportation service user decisions. Services has a significant effect on Gojek transportation service user decisions. Promotion has a significant effect on the decision of Gojek transportation service users.